Credit Granting: A Comparative Analysis of Classification Procedures: Discussion - Eisenbeis, Robert A. (Journal of Finance, 1987)
Robert A. Eisenbeis, Credit Granting: A Comparative Analysis of Classification Procedures: Discussion, The Journal of Finance, Vol. 42, No. 3, Papers and Proceedings of the Forty-Fifth Annual Meeting of the American Finance Association, New Orleans, Louisiana, December 28-30, 1986 (Jul., 1987), pp. 681-683